Guideline for increasing shops in Mahasarakham province to use the service Hom Chan Application of the Agricultural Bank and Agricultural Cooperatives - Intarakamhang , Jakrapong (Journal for Developing the Social and Community, 2022)
This study aimed to find factors affecting the decision to use Hom Chan, merchant’s application payment system, application for merchants to receive electronic payments. The results of the study will be used to plan a marketing strategy to increase user stores. The samples used in the study were the operators of 300 various types of shops in 13 district in Maha Sarakham province, including 13 district the study found a market factor that affected the use of the application to be trustworthiness of the bank services. And ask about perception in order to use Hom Chan, merchant’s application is receive relationship from the bank’s employee. Therefore, in order to increase the number of users of the Hom Chan merchant application, The bank should promote communication and public relations with customers with emphasis on social media services and media advertising to bolster safety and stability of applications and to build customer trust.